The land of open graves: living and dying on the migrant trail - De León, Jason (California series in public anthropology, 2015)
"Anthropologist Jason De León sheds light on one of the most pressing political issues of our time--the human consequences of US immigration policy. The Land of Open Graves reveals the suffering and death that take place daily in the Sonoran Desert of Arizona as thousands of undocumented migrants attempt to cross from Mexico into the United States. Drawing on the four major fields of anthropology, De León uses an innovative combination of ethnography, archaeology, linguistics, and forensic science to produce a scathing critique of 'Prevention through Deterrence,' the federal border enforcement policy that encourages migrants to cross in areas characterized by extreme environmental conditions and high risk of death. For two decades, this policy has failed to deter border crossers while successfully turning the rugged terrain of southern Arizona into a killing field"--Provided by publisher